Investigation of the effect of varying media properties and lubrication in media finishing - Chua, Zhen Qin (2015)
Media finishing is a subset of vibratory finishing where metallic components are processed in a circulatory flow of loose abrasive pellets called media to improve various surface properties through abrasive contact. The popularity of media finishing processes have grown significantly in recent years, leading to increased interest in optimising the parameters employed in the industry. An experimental investigation into the media finishing process was performed by varying different parameters of the media pellets such as shape and size, as well as process parameters such as work-piece orientation and degree of lubrication employed. The key performance indicator was the surface roughness average (Ra) value. Surface roughness measurements were taken using the Taly-scan profilometer. Experimental results were then analysed to obtain a better understanding of the main parameters influencing the results of the media finishing process. Results suggest that media shape is one of the key factors influencing resultant surface roughness values. The level of lubrication also plays a large role in vibratory finishing and should not be neglected. In comparison, work-piece orientation seems to have a relatively low impact on the process.